2019
DOI: 10.1002/sim.8111
|View full text |Cite
|
Sign up to set email alerts
|

Gene‐based sequential burden association test

Abstract: Detecting the association between a set of variants and a phenotype of interest is the first and important step in genetic and genomic studies. Although it attracted a large amount of attention in the scientific community and several related statistical approaches have been proposed in the literature, powerful and robust statistical tests are still highly desired and yet to be developed in this area.In this paper, we propose a powerful and robust association test, which combines information from each individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In this study, variant association analysis indicated the existence of moderate genomic inflation between these two cattle breeds, and no associated SNPs were detected. Therefore, based on advantages in detecting associations such as higher efficiency (greater detection power, and lower criteria for multiple testing) (Chen and Wang, 2019), a gene-based association strategy was used to identify physical traits associated with specific genes. Three gene-based methods (SKAT, SKATO, and Burden) showed there was moderate genomic inflation and that no gene could pass the threshold of the Bonferroni correction P-value.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, variant association analysis indicated the existence of moderate genomic inflation between these two cattle breeds, and no associated SNPs were detected. Therefore, based on advantages in detecting associations such as higher efficiency (greater detection power, and lower criteria for multiple testing) (Chen and Wang, 2019), a gene-based association strategy was used to identify physical traits associated with specific genes. Three gene-based methods (SKAT, SKATO, and Burden) showed there was moderate genomic inflation and that no gene could pass the threshold of the Bonferroni correction P-value.…”
Section: Discussionmentioning
confidence: 99%
“…As a secondary data analysis, we also considered sex as the only covariate to be adjusted in the logistic regression model. For comparison, we also reported the p-values from the score test S(x) (x = 0, 1 2 , and 1) and the LRT. Table 4 summarizes the results.…”
Section: Real Data Applicationmentioning
confidence: 99%
“…The goal of a genetic association study is to identify candidate genetic factors that are associated with specific disease status [1][2][3][4][5][6]. Toward this goal, a variety of statistical methods have been developed to test the association between disease and genetic variants [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…With recent advancements in biotechnologies, huge amount of data has been generated in genetics and genomics studies. For instance, in genomewide association studies (GWAS) to identify genetic risk factors associated with given disease, many gene-or set-based association tests have been developed which utilize the approaches for combining p-values [10][11][12][13][14] . How to combine these p-values is still a challenging topic in the area.…”
mentioning
confidence: 99%